Identification of the young stellar clusters in the G345.5+1.5 Star-Forming Region - Khachatryan, A.; Nikoghosyan, E.; Andreasyan, D.; Samsonyan, A.; Azatyan, N.; Grigoryan, V.; Simonyan, R.
Star-forming regions, their formation and evolution are a subject of active study. The subject of our research is the G345.5+1.5 region, which is composed of two dusty ring-like structures referred to as G345.45+1.5 and G345.10+1.35. The region is located at a distance of 1.8 kpc and classified as HII regions. According to previous studies, G345.45+1.5 could have been created by a supernova explosion represented by the 36.6 cm source J165920-400424 in its center. Despite the considerable interest, only a few works are devoted to this region, and there is very little information about its stellar population. Our work focuses specifically on the stellar population in this region. Using 2MASS astrometric and photometric data, we identified three well-defined clusters of young stellar objects (YSOs) in the vicinity of the IRAS 16561-4006, 16571-4029, and 16545-4012 sources.
Keywords: Astrometry; Space Sciences; Archaeoastronomy and Astronomy in Culture